Framing Berita Kenaikan Tunjangan DPR: Analisis Etika Komunikasi Islam - Rizqiyah, Luluk Ainur (UIN Sunan Ampel Surabaya, 2025)
The increase of allowances for members of the Indonesian House of Representatives (DPR) during August 2025 triggered public debate due to perceptions of inequality and lack of transparency. Kompas.com framed this issue as a moral and social concern, emphasizing the gap between the welfare of political elites and the economic conditions of citizens. This study applies a constructivist approach and Robert N. Entman’s framing analysis to explore four key elements: define problems, diagnose causes, make moral judgment, and treatment recommendation. Data were collected from news articles published on Kompas.com between August 19 and September 8, 2025. Findings reveal that Kompas.com defines the core problem as the dissonance between DPR’s financial privileges and public economic realities. The media attributes the cause to structural opacity, elitist political culture, and a lack of moral empathy among legislators. Moral judgment highlights the ethical responsibility of public officials and the social implications of their decisions, framing the issue as a test of integrity and legitimacy. In terms of recommendations, Kompas.com emphasizes the need for transparency, accountability, and moral reform, urging DPR to improve communication and align policy decisions with public welfare. Overall, Kompas.com constructs narratives that not only report facts but actively shape public perception and awareness, reinforcing the media’s role as a guardian of social ethics and democratic accountability. In Islamic communication ethics, the controversy over DPR allowances reflects weak ‘qaulan sidīdan’ and tabayyun as the information required corrections. The lack of transparency indicates a failure of amanah, while the delivery of the policy was seen as lacking empathy and justice (qaulan ma‘rūfan, al-‘adl). The media plays the role of ‘hisbah’ by encouraging public oversight. The core issue lies in a crisis of honesty and moral sensitivity. The solution is transparency, honest clarification, and public-oriented communication.